Pemanfaatan Limbah Serat Kelapa Sebagai Bahan Tambahan Pembuatan Paving Block - Rahmawati, Winda; Marcus, Patrice Kevin; Wisnu, Febryan Kusuma; Haryanto, Agus; Telaumbanua, Mareli; Sugianti, Cicih (abe.fp.unila.ac.id, 2024)
Indonesia is one of the largest coconut producing countries in the world, Lampung Province itself has a coconut plantation area of 91.8 thousand hectares with a production of 81.9 thousand tons in 2021. One alternative of the uses of coconut fiber is as a mixing material for porous paving blocks. This study aims to make porous paving blocks with additional coconut fiber and to determine the physical characteristics of paving blocks with a mixture of coconut fiber. This study used a completely randomized design consisting of 4 treatments and 5 replications with a sample size of 40 pieces divided into destructive and non-destructive tests. The method of making paving blocks in the study was that the fiber was mixed with a mixture of cement and sand, then molded and conditioned for 28 days. The tests carried out were visual tests, water absorption tests, infiltration tests, density tests and compressive strength tests. The results of the study showed that the addition of coconut fiber to the paving block mixture affected the results of the test of the characteristics of porous paving blocks) Keywords: Coconut Fiber, Deformation, Ductile, Infiltration, Pore Space.